Development of Digital Comic Media on Pancasila Values Material to Improve Civic Disposition of Grade - Miza Nur Amalia; Syailin Nichla Choirin; Hamidaturrohmah (JPG: Jurnal Pendidikan Guru, 2025)
This study aims to design digital learning media using digital comics that are expected to increase students' civic disposition towards Pancasila values. The approach applied is research and development with the ADDIE model as the methodology. The research subjects involved 36 fourth grade students of SDN Kauman. Data collection techniques were applied using observation, interviews and questionnaires. The research instruments were observation sheets, interviews, material and media expert validation, teacher and student response questionnaires and civic disposition questionnaires for pre and post tests. Data analysis was done through T-test and paired sample t-test. The results indicated that the product was rated very feasible by the media experts 96% and 96% by the material experts. the practicality score value of the teacher's response reached 71% and 81% students including the “good” category. The paired sample t-test showed the average pre-test score was 77.3 while the average post-test score increased to 83.5 reflecting a significant increase. The paired sample t-test shows a significant difference between the pre-test and post-test scores, proving that the digital learning media developed is feasible, practical and effective in increasing civic position in Pancasila education learning.